2017
DOI: 10.1021/acs.jpcc.7b01385
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Photo-Oxidation on Rutile TiO2 Nanowires: Probing Reaction Pathways on Complex Materials

Abstract: Understanding photochemical processes on nanomaterials is key to developing effective photocatalysts. Herein, methanol oxidation and reduction is used to probe the thermal and photochemical properties of rutile titania nanowires grown using a hydrothermal method. The presence of oxygen vacancy defects leads to methoxy formation and subsequent disproportionation to formaldehyde and methanol at 700 K. Methane and dimethyl ether are also produced in minor quantities. Oxygen adatoms enhance the formation of methox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…The results from the temperature‐programmed reaction experiments suggested that the methoxy was transformed through photo‐oxidation to HCHO and HCOOCH 3 . Next, a similar phenomenon was observed on the rutile TiO 2 nanowires in the methanol photo‐oxidation [26] …”
Section: Reaction Pathway Of Methanolsupporting
confidence: 67%
“…The results from the temperature‐programmed reaction experiments suggested that the methoxy was transformed through photo‐oxidation to HCHO and HCOOCH 3 . Next, a similar phenomenon was observed on the rutile TiO 2 nanowires in the methanol photo‐oxidation [26] …”
Section: Reaction Pathway Of Methanolsupporting
confidence: 67%
“…The reactivity measurements were carried out in an ultrahigh vacuum (UHV) apparatus with a base pressure of < 8×10 -11 Torr, which has been described in detail before. [27][28] The α-Fe 2 O 3 (0001) single crystal (SurfaceNet GmbH) is mounted as described previously and the sample temperature can be controlled between 130 K and 1000 3 K. 28 Crystal cleaning is accomplished by Ar + -ion sputtering (1.0 keV, 1.0 × 10 -5 Torr, 15 min, 13 µA sample current) and annealing in vacuo (1000 K, 15 min). Before every experiment, 3 cycles of sputtering and annealing are performed to remove all potential contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature-programmed desorption and reaction measurements were performed with the crystal in line-of-sight of the quadrupole mass spectrometer with a constant heating rate of 1 K/s. The masses monitored were m/e 2, 15,16,18,27,28,29,30,31,32,33,35,44,46,47,79,124. The gaseous products were identified by their fragmentation patterns and quantified by correcting for mass spectrometer sensitivity the ionization cross sections.…”
Section: Methodsmentioning
confidence: 99%
“…With the introduction of O 2 ,O 2 -promoted CH 3 OH(a) dissociation to CH 3 O(a) [27] was observed to occur only slightly for all TiO 2 NCs under the dark condition (Supporting Information, Figure S10). Upon UV light illumination, the absorption feature of photoexcited electrons greatly decreased with the O 2 concentration increasing and became similar for all TiO 2 NCs at an oxygen concentration of 10 % (Supporting Information, Figure S11), demonstrating the efficient scavenging of photoexcited electrons by O 2 .C onsequently,p hotocatalytic oxidation of adsorbed CH 3 O(a) species to HCOO(a), HCHO(a) and carbonate species occur on all TiO 2 NCs,a se videnced by the appearance of the vibrational features of various types of HCOO(a) and carbonate species and HCHO(a) species [13,28] at the expense of those of CH 3 O(a) species (Supporting Information, Figure S12, Table S1).…”
Section: Forschungsartikelmentioning
confidence: 99%